Prevalence, Awareness, Treatment, and Control of Hypertension and Its Associated Risk Factors: Results from Baseline Survey of SWADES Family Cohort Study - M. D. Saju; Komal Preet Allagh; Lorane Scaria; Shinto Joseph; Jotheeswaran Amuthavalli Thiyagarajan (International Journal of Hypertension)
Introduction. Hypertension is one of the most important modifiable risk factors for cardiovascular diseases. The objective of this study is to estimate the prevalence, awareness, treatment, and control of hypertension and its associated risk factors in Ernakulam district, Kerala. Methods. In this prospective family-based cohort study, 573 families were included with a total of 997 participants aged 30 years and above. Baseline interviews were conducted in participant’s homes using a combination of self-structured and standardized questionnaire. Blood pressure and plasma glucose were assessed for each participant. Results. The prevalence of hypertension was 43%. It was slightly higher in women than men (43.7% vs. 41.4%). The mean systolic blood pressure in the hypertensive population was 141.9 mmHg and mean diastolic blood pressure was 85.3 mmHg. In total, 78% (86.2% in women, 62.9% in men) of the participants were aware of their hypertension. Among those aware, 60.4% (63.5% in women, 52.6% in men) of the participants were on treatment, and hypertension was controlled in 75.1% (77.5% women, 68% in men) of the participants on treatment. The prevalence of hypertension was higher among persons with comorbidities (diabetes 64.5%, transient ischemic attack 54.7%, and heart disease 64.4%). Prevalence was lower among persons who did regular vigorous intensity exercise versus those who did moderate intensity exercise (32% vs. 45.7%) and among nonsmokers versus smokers (42.2% vs. 46.6%). Conclusion. The prevalence of hypertension in Kerala is high. Although awareness is quite high, there is a need to improve the number of persons with hypertension taking treatment.